Impact of aging on food consumption in rural China: Implications for dietary upgrading and health improvement - Gao, Ming; Wu, Bi; Jin, Wencheng; Wei, Jiashuo; Wang, Jiwen; Li, Jinkai (Frontiers in Nutrition, 2022)
The issue of population aging in rural China is getting worse, whereas its impact on food consumptions has not been well evaluated. Using nationally representative household-level data from the China National Fixed Rural Observation Site Survey in 2020, this paper studies the im-pact of aging on food consumption in rural households and get findings as follows: (1) The proportion of rural residents’ major food consumption in 2020 is meat and products (36.8%), grain (24.5%), vegetables (10.9%), respectively. (2) Increase in the number of older adults improves food consumption on poultry, aquatic products, eggs, milk and dairy products. (3) Due to the difference of young adults’ food consumption structure, older adults would increase their consumption on fruits and vegetables if they live with younger adults together. The findings of this study suggest that rural older adults should increase consumption on fruits and vegetables while maintaining the intake of protein, so as to keep the balance of dietary structure and improve older adults’ health condition.